Algae : an introduction to phycology - Hoek, C. van den (Christiaan); Mann, D. G.; Jahns, Hans Martin (Cambridge ; New York : Cambridge University Press, 1995)
Algae are ubiquitous. A multitude of species, ranging from microscopic unicells to gigantic kelps, inhabit the world's oceans, freshwaters, soils, rocks and trees. To understand the basic role of algae in the global ecosystem, a reliable and modern introduction to their kaleidoscopic diversity, systematics and phylogeny is indispensable. This volume provides such an introduction.
24. Chlorophyta: Class 5. Bryopsidophyceae -- 25. Chlorophyta: Class 6. Dasycladophyceae -- 26. Chlorophyta: Class 7. Trentepohliophyceae -- 27. Chlorophyta: Class 8. Pleurastrophyceae, and the order Prasiolales (Appendix to the classes with an 11 o'clock - 5 o'clock configuration of the basal bodies) -- 28. Chlorophyta: Class 9. Klebsormidiophyceae -- 29. Chlorophyta: Class 10. Zygnematophyceae -- 30. Chlorophyta: Class 11. Charophyceae -- 31. Reflections on the phylogeny of the Chlorophyta -- 32. Phylogenetic reflections on the algae.
"First published 1995"--T.p. verso.
"Published in an abridged German edition by George Thieme Verlag, Stuttgart as Algen, c1978, 1993"--T.p. verso.
Includes bibliographical references and index.
Keywords: Algology; Algae